Readiness for online learning during Covid-19 pandemic in the vocational education - M., Muktiarni; A. Rashid, Ana Haziqah; Barliana, Mokhamad Syaom; Saleh, Ilhamdaniah; Mulyadi, Yadi; Salira, Ade Budhi; Sari, Ana Ramdani; Masek, Alias; Paimin, Aini Nazura; Ab Halim, Fazlinda; Wan Muda, Wan Hanim Nadrah (2022)
This study was designed to see the learning readiness of vocational education students who were carried out online during the Covid-19 pandemic. Vocational education which has a peculiarity is the mastery of skills, so we want to see the extent of students' readiness to carry out online learning. In a quantitative research approach with a survey method, a survey was conducted on 247 vocational education students via a google form. The collected data were analyzed, then the results of the study revealed that students were fully ready to carry out online learning, starting with digital literacy, independent learning, and communication. Overall students are ready to do online learning, Judging from the characteristics of vocational education, there is practicum material that can be handled by the use of several supporting learning media. But in controlling themselves during the learning process (learning control), students have not been able to fully control themselves during the learning process. The online learning process provides various facilities for students, but still, the teacher has a role as a guide and guides students so that the learning process is following the expected goals.